2020
DOI: 10.21203/rs.2.24266/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Medical cannabis use in the Australian community following introduction of legal access: The 2018-2019 Online Cross-Sectional Cannabis as Medicine Survey (CAMS-18)

Abstract: Background : In 2016 the Australian federal government passed legislation enabling a range of cannabis-based products to be prescribed to patients by registered healthcare professionals. An online survey conducted immediately prior to these legislative changes found that the vast majority of respondents at the time were illicitly sourcing cannabis plant matter, smoking was the preferred route of administration, and mental health, chronic pain, and sleep conditions were the most frequently cited reasons for med… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 5 publications
3
48
0
Order By: Relevance
“…36 The reasons for this may include the high cost of unregistered cannabisbased products compared to illicit cannabis (which is often home-grown), the inability to find a doctor who will assist in making an application to the TGA, lack of knowledge of official access pathways, and a reticence to discuss cannabis use with a doctor. 34,35 Illicit cannabis products are likely to be suboptimal as therapeutics. They probably contain a great deal of THC and little CBD 37 and may also contain contaminants such as pesticides and heavy metals.…”
Section: Current and Future Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…36 The reasons for this may include the high cost of unregistered cannabisbased products compared to illicit cannabis (which is often home-grown), the inability to find a doctor who will assist in making an application to the TGA, lack of knowledge of official access pathways, and a reticence to discuss cannabis use with a doctor. 34,35 Illicit cannabis products are likely to be suboptimal as therapeutics. They probably contain a great deal of THC and little CBD 37 and may also contain contaminants such as pesticides and heavy metals.…”
Section: Current and Future Challengesmentioning
confidence: 99%
“…Despite the exponential rise in approvals under the SAS-B scheme, surveys suggest that many Australians continue to self-medicate with illicit cannabis. 34 , 35 Indeed, the National Drug Strategy Household Survey recently reported that 600,000 Australians use cannabis for medicinal purposes, but only 3.9% obtain it via legal pathways. 36 The reasons for this may include the high cost of unregistered cannabis-based products compared to illicit cannabis (which is often home-grown), the inability to find a doctor who will assist in making an application to the TGA, lack of knowledge of official access pathways, and a reticence to discuss cannabis use with a doctor.…”
Section: Current and Future Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…88 An Australian survey of 1388 medicinal cannabis users listed a similar range of indications, including pain (62%), sleep (49%), mental health (45%), gastrointestinal disorders (13%), neurological disorders (11%) and cancer (8%). 89 However, the evidence base for most of these putative indications is limited, with the exception of anxiety. A recent systematic review identified six randomized pre-clinical studies in this area.…”
Section: Effects Of Cbd On Anxietymentioning
confidence: 99%
“…This survey was then repeated in 2018 (CAMS-18, n=1388). 98 The majority of participants in the CAMS-16 survey, who predominantly used illicit cannabis for medicinal symptoms indicated that they believed that cannabis should be legal for all uses (88.8%). 97 A further 11.0% indicated it should be legal for medical purposes only, with approximately 90% indicating they 'strongly agreed or agreed' that medicinal cannabis should be part of routine health care in Australia.…”
Section: Patient Demand For Cannabis-based Productsmentioning
confidence: 99%